Portrayal of a male deity depicted with three heads wearing Jatamukutas - Temples of India Project Team (Jio Institute, 2024)
Adjacent to the representation of Vayu on the northern wall of the garbhagriha (sanctum sanctorum), there is a portrayal of a male deity depicted with three heads wearing jatamukutas (crowns of matted hair). Originally having four arms, only three are currently preserved. In his foremost hand, he holds a bowl close to his chest, and with another hand, he touches the bowl. His third hand is positioned in the varada hasta (boon-giving) gesture.